Acute Toxicity and Gastroprotective Role of M. pruriens in Ethanol-Induced Gastric Mucosal Injuries in Rats - Shahram Golbabapour; Maryam Hajrezaie; Pouya Hassandarvish; Nazia Abdul Majid; A. Hamid A. Hadi; Noraziah Nordin; Mahmood A. Abdulla (Hindawi Publishing Corporation, 2024)
Volume 2013